Imaging diagnosis for bone invasion by gingival carcinoma of the mandible: The value and the limitation - Eiji Nakayama (Elsevier, 2009)
The bone invasion in carcinoma of the mandibular gingiva (CaMG) is one of the important factors to determine the treatment planning and predict the prognosis. Japan Society for Oral Tumors proposed a new criterion of T4 classification of CaMG in 1997 as follows: the tumor is classified as T4 when the tumor spreads into the mandibular canal, and the tumor should not be classified as T4 when the tumor does not invade into the mandibular canal. Thus, the supero-inferior extent of bone invasion is one of the important diagnostic factors on Images. The accuracy of the supero-inferior extent of bone invasion by diagnostic images is equal between panoramic radiography (PR) and CT, and hence, PR would be suitable for the initial screening modality to survey the bone invasion into the mandibular canal. However, regarding the pattern of bone invasion by CaMG, the CT pattern of bone invasion is associated with the prognosis, and therefore the pattern should be determined based on the CT findings. In conclusion, at the present time, CT is suitable for detection of bone invasion in CaMG, although CT cannot detect precisely an early weak bone invasion, or a bone invasion infiltrating through the trabecular bone.